(3GdYeOI aj CUhd GdOjfs - (3YHO Gddg Hf CMeO Hf eMehO GdfSaj, CHh GdHQcGJ, MGaX GdOjf,J (B710 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf gPG GdeNJUQ YeOI YbjOI Cgd GdSfI hGdLeGYI bGd Cgd GdMb MbGFb GdCTjGA KGHJI dCf ai fajgG KHhJgG hGdYde HgG eJMbb s
(3BNQgG (B:s
(3Pi GdfhQjf QVi Gddg Yfg Ke Ydi Ydi GdeQJVi QVi Gddg Yfg hYdi gPG JQJjHge ai GdaVjdI hbO bGd Ydjg GdSdGe GdNdGaI HYOi KdGKhf SfI hbO JeJ HYdi QVi Gddg Yfg aUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHI hSde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B32s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1168s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs